2019
DOI: 10.3390/app9245402
|View full text |Cite
|
Sign up to set email alerts
|

Ballast Flow Characteristics of Discharging Pipeline in Shield Slurry System

Abstract: We adopted two-way coupling of discrete and finite elements to examine the non-spherical ballast flow characteristics in a slurry pipe system during a shield project. In the study, we considered the slurry rheological property and the flake shape of the ballast. A ballast size between 17 and 32 mm under different slurry flow rates and ballast volumetric concentration conditions was investigated for determining the law through which the mass flow rate, detained mass percentage, and ballast distribution state ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In addition, we further verified the biosafety of our phenolic HA patches in vitro and in vivo. We previously demonstrated that various primary cells and stem cells including hepatocytes, endothelial cells, neural stem cells, and mesenchymal stem cells were highly viable in HA‐CA hydrogels during culture 7a,8,38. We also reported that hADSCs grown within gallol‐modified HA hydrogel showed good viability more than 95% 7b.…”
Section: Resultsmentioning
confidence: 90%
“…In addition, we further verified the biosafety of our phenolic HA patches in vitro and in vivo. We previously demonstrated that various primary cells and stem cells including hepatocytes, endothelial cells, neural stem cells, and mesenchymal stem cells were highly viable in HA‐CA hydrogels during culture 7a,8,38. We also reported that hADSCs grown within gallol‐modified HA hydrogel showed good viability more than 95% 7b.…”
Section: Resultsmentioning
confidence: 90%
“…With the burgeoning development in bioprinting techniques, it is expected that current limitations of spatial resolution, throughput, printability and biocompatibility will be diminished. Novel bioprinting approaches including scaffold‐free printing (direct 3D deposition and assembly of cells and cell spheroids into guided tissue architectures), [ 235,236 ] nanoscale matrix fabrication (electrospun fibers in bulk gels for guided EC assembly), [ 237–242 ] 4D printing (stimulus‐responsive materials that undergo programmed 3D conformational change over time postprinting) [ 243,244 ] and acoustophoretic printing (user‐controlled surface acoustic wave forms to pattern cell‐laden hydrogels in 3D space) [ 245,246 ] can also provide potential opportunities for fabrication of complex vascular networks. Further integration of bioprinted constructs with microfluidic platforms will facilitate the interrogation of vascular mechanobiology in organ‐mimetic microenvironments.…”
Section: Fabrication Strategies To Generate Microfluidic and Vascularmentioning
confidence: 99%
“…Wang et al [10] used two-way coupling of FEM-DEM to check the characteristics of anomalistic ballast flow in slurry circulation system in the process of tunneling. The ballast size of 17~32 mm under various slurry velocities and ballast particle volume concentrations was studied to determine the impact law of slurry velocities, retention quality percent and ballast distribution.…”
Section: Introductionmentioning
confidence: 99%